2004
DOI: 10.1128/aac.48.1.137-142.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of a New Triazole, Posaconazole, in a Murine Model of Disseminated Candidiasis

Abstract: Previous in vivo studies have characterized the pharmacodynamic characteristics of two triazole compounds, fluconazole and ravuconazole. These investigations demonstrated that the 24-h area under the concentrationtime curve (AUC)/MIC ratio is the critical pharmacokinetic-pharmacodynamic (PK-PD) parameter associated with treatment efficacy. Further analysis demonstrated that a free-drug triazole 24-h AUC/MIC ratio of 20 to 25 was predictive of treatment success in both experimental models and clinical trials. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
130
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 24 publications
11
130
1
5
Order By: Relevance
“…[76][77][78] Although less data are available for other triazoles and mold infections, studies in animal models of aspergillosis also suggest that the AUC:MIC ratio is the best predictor of treatment response to posaconazole, with 50% survival at total-drug AUC:MIC ratios of 100 to 150 and maximal responses at a ratio greater than 440 (free-drug AUC:MIC ratio of approximately 8-25). 79,80 Clinical trial data for candidal infections have suggested that this pharmacokinetic-pharmacodynamic relationship may be helpful for predicting treatment efficacy in For personal use. Mass reproduce only with permission from Mayo Clinic Proceedings a .…”
mentioning
confidence: 99%
“…[76][77][78] Although less data are available for other triazoles and mold infections, studies in animal models of aspergillosis also suggest that the AUC:MIC ratio is the best predictor of treatment response to posaconazole, with 50% survival at total-drug AUC:MIC ratios of 100 to 150 and maximal responses at a ratio greater than 440 (free-drug AUC:MIC ratio of approximately 8-25). 79,80 Clinical trial data for candidal infections have suggested that this pharmacokinetic-pharmacodynamic relationship may be helpful for predicting treatment efficacy in For personal use. Mass reproduce only with permission from Mayo Clinic Proceedings a .…”
mentioning
confidence: 99%
“…In a mouse model of invasive candidiasis, treatment with a single dose of posaconazole resulted in prolonged inhibition of fungal growth for at least 20 h after the free drug concentration decreased below the MIC of the infecting strain. 12 Prolonged suppression of C. albicans growth was also observed even with a dose of posaconazole that did not result in serum free drug concentrations above the MIC at any point during therapy. 12 Similarly, in a study of A. fumigatus infection in mice, the authors noted that the drug exposure required to achieve stasis and killing of A. fumigatus was lower than that observed in similar studies of other triazoles.…”
mentioning
confidence: 88%
“…12 Prolonged suppression of C. albicans growth was also observed even with a dose of posaconazole that did not result in serum free drug concentrations above the MIC at any point during therapy. 12 Similarly, in a study of A. fumigatus infection in mice, the authors noted that the drug exposure required to achieve stasis and killing of A. fumigatus was lower than that observed in similar studies of other triazoles. 13 How can we resolve this apparent discrepancy between relatively low serum posaconazole levels yet documented antifungal efficacy?…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…En el caso de los azoles no se dispone de información clínica relevante, aunque en los modelos de animales vivos, es la relación AUC con la CMI (AUIC), el parámetro que mejor predice la eficacia de estos antifúngicos. Los estudios realizados parecen señalar que el valor óptimo del AUIC se sitúa en 20 [1,2]. La comparación de las AUC (Tabla1) permite comprobar las diferencias en el valor AUC/CMI de los diferentes azoles si se utiliza en el cálculo el mismo valor para la CMI.…”
Section: Características Farmacocinéticasunclassified